Antibiotic use for pneumonia among children under-five at a pediatric hospital in Dhaka city, Bangladesh - Rashid, Md Mahbubur; CHISTI, M. J.; Akter, Dilruba; Sarkar, Malabika; Chowdhury, Fahima Rabbi (© 2017 Dove Medical Press Ltd., 2018)
This article was published in the Patient Preference and Adherence [© 2017 Rashid et al.] and the definitive version is available at : https://doi.org/10.2147/PPA.S140002 The Journal's website is at: https://www.dovepress.com/antibiotic-use-for-pneumonia-among-children-under-five-at-a-pediatric--peer-reviewed-article-PPA